Montagem e teste de um novo arranjo do dessalinizador solar térmico de múltiplos estágios com recuperação de calor - Dutra, Kaio Hemerson (2016)
Access to fresh water is now a clear and growing problem, only 2.5% of the planet's water is potable, however, from this small portion 79.16% is in glaciers, or unavailable. Associated with the water supply problem, there is the need for diversification of energy sources, due to the increasing cost and depletion of conventional energies. The use of solar energy in desalinators is an alternative to access fresh water to isolated communities that may not have adequate infrastructure. The objective of this work was to assemble and test a multi-stage solar desalination with heat recovery and indirect heating, as well as facilitate and ensure their satisfactory operation. The desalinator is composed of two units, the first called heating unit consists of solar collectors and can be assembled in two configurations with two or three collectors. Each collector has 2.57 m² of useful area of solar energy absorption. The second is called desalination unit composed of a water storage tank and until seven stages in series. Brackish water is heated in the heating unit and the density difference, through a thermosyphon loop, flows into desalination tower where it is stored and evaporated, losing heat and returning to the heating unit, closing the cycle. The evaporated mass comes into contact with a tray of the first stage, loses heat to the stage above and condenses, the distillate is collected by gutters beneath the tray. For evaluation of the system, tests of heating and production have been carr ied out. The heating test in order to evaluate the capability of the heating unit was conducted with two and three collectors, in both configurations, the results were satisfactory, with temperatures above 90 ° C. Production tests evaluated the desalinated water production system, several configurations were tested, obtaining a maximum output of 42 liters per day using three collectors and seven stages.